The Effect of Self-Control, Emotional Intelligence, and Parenting Style on Student Discipline in Learning Pancasila Education - Aprianti, Affi; Prasetiyo, Wibowo Heru (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to examine the effect of self-control on student discipline within the context of Pancasila Education at SMAN 1 Karangnongko. Furthermore, it seeks to assess the influence of emotional intelligence and parenting styles on student discipline within the same educational environment. Methodology: This research employed a quantitative approach with a correlational research design. The sample consisted of 271 students from grades X and XI at SMAN 1 Karangnongko. Results: The results indicate that self-control, emotional intelligence, and parenting styles have a significant impact on student discipline in Pancasila Education at SMAN 1 Karangnongko. Applications/Originality/Value: This study contributes to the existing literature by elucidating the relationships among self-control, emotional intelligence, and parenting styles in relation to student discipline, providing a foundation for future research in this field.